Step 1) Solve the first equation for x:
x + 4y - color(red)(4y) = 8 - color(red)(4y)
x + 0 = 8 - 4y
x = 8 - 4y
Step 2) Substitute 8 - 4y for x in the second equation and solve for y:
2x - 5y = 29 becomes:
2(8 - 4y) - 5y = 29
(2 xx 8) - (2xx4y) - 5y = 29
16 - 8y - 5y = 29
16 - 13y = 29
-color(red)(16) + 16 - 13y = -color(red)(16) + 29
0 - 13y = 13
-13y = 13
(-13y)/color(red)(-13) = 13/color(red)(-13)
(color(red)(cancel(color(black)(-13)))y)/cancel(color(red)(-13)) = -1
y = -1
Step 3) Substitute -1 for y in the solution to the first equation at the end of Step 1 and calculate x:
x = 8 - 4y becomes:
x = 8 - (4 xx -1)
x = 8 - (-4)
x = 8 + 4
x = 12
The solution is x = 12 and y = -1 or (12, -1)